Systematic Literature Review: Using Mind Mapping to Improve Students' Creative Thinking Abilities - Faradiba P, St. Asyah Alya; Arsad BAHRI (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
This research aims to explore the influence of mind mapping on improving students' creative thinking abilities. Through a Systematic Literature Review (SLR) approach, this article collects and analyzes relevant research results to provide a comprehensive picture of this topic. The results of the study show that mind mapping helps students organize information visually, which makes it easier for them to see relationships between concepts more clearly and holistically. The use of mind mapping has also been proven to stimulate students' creativity by encouraging them to think divergently and produce various new ideas. Additionally, mind mapping facilitates collaboration among students, allowing them to share ideas and work together on group projects, which is important for the development of creative thinking skills. By helping students see the relationships between concepts more clearly and holistically, mind mapping has proven to be effective in improving creative thinking abilities. Therefore, it is recommended that the integration of mind mapping in the learning process be implemented more widely in the educational curriculum. Teacher training regarding mind mapping techniques is also an important factor in ensuring effective and optimal implementation and improving students' creative thinking abilities. Thus, mind mapping not only functions as a learning tool but also as an effective method for developing students' overall creative potential.